The combination of transcriptome and metabolome reveals the molecular mechanism by which topping and salicylic acid treatment affect the synthesis of alkaloids in Nicotiana tabacum L. Issue 1 (31st December 2022) - Zhang, Mengyue; Zhao, Yuanyuan; Yang, Chunting; Shi, Hongzhi
Abstract : Topping and salicylic acid (SA) treatment are thought to change nicotine content in Nicotiana tabacum L. (tobacco). This study aimed to investigate the potential underlying molecular mechanisms. Tobacco variety K326 plants were divided into four groups, each receiving only the topping treatment (TW), the topping and 0.6 mM SA treatment (TS), the 0.6 mM SA treatment only (NS), and no treatment (control group, NW). The content of alkaloids and expression of genes related to nicotine synthesis were determined through gas chromatography-hydrogen flame ionization and liquid chromatography mass spectrometry. Differentially expressed and differentially expressed genes (DEGs) were screened and analyzed between different groups. Finally, we constructed a DEG-pathway-differential metabolite network using Cytoscape. While SA treatment decreased the expression of genes related to nicotine synthesis and alkaloid content, topping showed the opposite results: transcriptome and metabolome analyses showed that both changed a variety of biological pathways and related gene expression in tobacco, including arginine and proline metabolism, tropane, piperidine and pyridine alkaloid biosynthesis, nicotinate and nicotinamide metabolism, glutathione metabolism, biotin metabolism, phenylpropanoid biosynthesis, and plant hormone signal transduction. This study provides new insights for understanding how topping and SA treatment affect nicotine content in tobacco and provides a direction for future breeding.